Talent management in the public sector – empirical evidence from the emerging economy of Romania - Barrington, Graham (Central European Public Administration Review, 2024)
Purpose: This paper aims to investigate how talent management is conceptualized and practised within Romanian public sector organizations. Just like their private sector counterparts, public sector organizations need talented employees or high performers to support their operations and enhance public service delivery. However, research on talent management in the public sector, particularly in Eastern European countries, remains limited. Design/Methodology/Approach: The study was conducted through a series of semi-structured interviews with employees in public sector organizations. The results were analysed using thematic analysis. Findings: The study reveals that talent management practices in the public sector are still in a nascent state of development. Furthermore, there appears to be a lack of understanding of talent management among HR practitioners, and implementation efforts have yielded less-than-desirable results. Practical Implications: The results of our study suggest that while talent management practices are widely embraced by a growing number of private sector companies, their conceptualization and implementation in the public sector differ. In the case of Romania, implementation is hindered by the bureaucratic structure of the public sector and the legacy of previous communist regime. Originality/Value: The study represents one of the initial attempts to investigate the impact of talent management practices in the Romanian public sector, leveraging empirical evidence to support its findingszeng - angleški aPurpose: This paper aims to investigate how talent management is conceptualized and practised within Romanian public sector organizations. Just like their private sector counterparts, public sector organizations need talented employees or high performers to support their operations and enhance public service delivery. However, research on talent management in the public sector, particularly in Eastern European countries, remains limited. Design/Methodology/Approach: The study was conducted through a series of semi-structured interviews with employees in public sector organizations. The results were analysed using thematic analysis. Findings: The study reveals that talent management practices in the public sector are still in a nascent state of development. Furthermore, there appears to be a lack of understanding of talent management among HR practitioners, and implementation efforts have yielded less-than-desirable results. Practical Implications: The results of our study suggest that while talent management practices are widely embraced by a growing number of private sector companies, their conceptualization and implementation in the public sector differ. In the case of Romania, implementation is hindered by the bureaucratic structure of the public sector and the legacy of previous communist regime. Originality/Value: The study represents one of the initial attempts to investigate the impact of talent management practices in the Romanian public sector, leveraging empirical evidence to support its findings
Keywords: javni sektor; public sector; talent; talent management; talenti; teorija birokracije; theory of bureaucracy; upravljanje talentov